New species of Orthocentrinae (Hymenoptera: Ichneumonidae) from Finland - Humala, Andrei (Entomologica Fennica, 2008)
Five new species of ichneumonids of the subfamily Orthocentrinae s. l. were discovered in Finnish collections. A new genus is proposed for one new species from Southern Finland, Fennomacrus koponeni gen. et sp. n. Its relationships and systematic position are briefly discussed. Four other new species, Plectiscidea aquilonia sp. n., P. fuscifemur sp. n., P. helleni sp. n. and Eusterinx (Holomeristus) fennoscandica sp. n., from Fennoscandia are also described. The hitherto unknown female of Helictes fabularis Rossem is described as well.